2010 43rd Hawaii International Conference on System Sciences 2010
DOI: 10.1109/hicss.2010.149
|View full text |Cite
|
Sign up to set email alerts
|

Digital Cross-Organizational Collaboration: A Metatriangulation Review

Abstract: This paper presents a metatriangulation review on the topic of digital cross-organizational collaboration, defined as the integration of people, information systems, and processes across different organizations to accomplish a particular task by using digital means as an enabler. Using paradigm lenses adapted from Markus and Robey (1988), we examine 80 research papers published in six information systems journals between 2000 and 2007. The results of our analysis suggest that the theoretical view points (techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…For instance, information sharing facilitates better decisions on ordering, capacity allocation, production and material planning through increased visibility of demand, supply and inventory (Iyer, Germain & Claycomb 2009;Madlberger & Roztocki 2010). Some studies (Chavez et al 2015;Forslund & Jonsson 2007;Soosay et al 2008) further suggest that information sharing leads to improved business performance through its role as the driver of competitiveness and supply chain effectiveness.…”
Section: Information Sharing and Supply Chain Performancementioning
confidence: 99%
“…For instance, information sharing facilitates better decisions on ordering, capacity allocation, production and material planning through increased visibility of demand, supply and inventory (Iyer, Germain & Claycomb 2009;Madlberger & Roztocki 2010). Some studies (Chavez et al 2015;Forslund & Jonsson 2007;Soosay et al 2008) further suggest that information sharing leads to improved business performance through its role as the driver of competitiveness and supply chain effectiveness.…”
Section: Information Sharing and Supply Chain Performancementioning
confidence: 99%
“…Similar is in higher education, where participants can use collaboration platforms and face-to-face communication tools. We see innovation lately in digital collaboration, which is driving efficiency and productivity with the combination of traditional tools, social media, and other modern tools that create unique, sustainable working environments [97]. In higher education, this is seen in the integration of collaboration platforms and tools with traditional e-learning platforms for access to digitalised content of courses.…”
Section: Attractiveness Of E-learning Collaboration Platforms For Stu...mentioning
confidence: 99%
“…Several studies have found that organization that has implemented IT integration have enhanced information sharing in may benefit from in various ways, which include a reduction in inventory levels, operational costs, automation of routine functions, better data documentation, and communication, etc. (Paulraj, Lado & Chen, 2008;Madlberger & Roztocki, 2010;Leuschner et al, 2013;Chavez et al, 2015).…”
Section: Literature Reviewsmentioning
confidence: 99%